The Influence of Invariant Natural Killer T Cells on Humoral Immunity to T-Dependent and -Independent Antigens - Lang, Mark L. (Frontiers in Immunology, 2018)
Vaccination with CD1d-binding glycolipid adjuvants and co-administered protein, lipid, and carbohydrate antigens leads to invariant NKT cell-dependent enhancement of protective B cell responses. NKT cell activation boosts the establishment of protein antigen-specific B cell memory and long-lived plasma cell compartments. NKT cells may exert a similar effect on some carbohydrate-specific B cells, but not lipid-specific B cells. The mechanisms of action of NKT cells on B cell responsiveness and subsequent differentiation into memory B cells and long-lived plasma cells is dependent on CD1d expression by dendritic cells and B cells that can co-present glycolipids on CD1d and antigen-derived peptide on MHCII. CD1d/glycolipid-activated NKT cells are able to provide help to B cells in a manner dependent on cognate and non-cognate interactions. More recently, a glycolipid-expanded subset of IL-21-secreting NKT cells known as NKT follicular helper cells has been suggested to be a driver of NKT-enhanced humoral immunity. This review summarizes established and recent findings on how NKT cells impact humoral immunity and suggests possible areas of investigation that may allow the incorporation of NKT-activating agents into vaccine adjuvant platforms.